Food insecurity among displaced populations in Armenia during the 2020 Nagorno-Karabakh conflict - Araz Majnoonian; Araz Majnoonian; Carine Tamamian; Musheh Ovanesian; Tala Al-Rousan (Frontiers in Public Health)
BackgroundThe 2020 Nagorno-Karabakh conflict resulted in displacement of approximately 90,000 ethnic Armenians from Nagorno-Karabakh to Armenia, exacerbating existing vulnerabilities in the region. This study investigated food insecurity among displaced populations and host communities in Armenia during the conflict.MethodsThis study is a secondary analysis of cross-sectional data obtained from the 2020 REACH ARM Database Multi-Sector Needs Assessment (MSNA), which was conducted across six Armenian provinces. The original data collection was designed to assess humanitarian needs in Armenia in the aftermath of the 2020 Nagorno-Karabakh conflict. In this analysis, we examined the associations between displacement status and two outcomes of interest: the household’s ability to purchase food and reduced portion sizes. Multivariable logistic regressions were performed for each food security outcome.ResultsThe study sample included 1,309 households, with most male heads (68.1%), an age distribution mostly under 50 years (81.2%), a majority having general education (55.7%) and higher education (22.8%), and 74.0% not employed. 134 households (10.2%) were displaced and staying in collective centers, 658 households (50.3%) were displaced and staying with family or friends, and 517 households (39.5%) that were not displaced but hosting displaced people. Displaced individuals staying in collective centers had 3.89 times higher odds of reporting a reduced ability to purchase food compared to non-displaced individuals (aOR: 3.89, CI: 2.396.45). Additionally, displaced individuals staying with friends or family had 2.5 times higher odds of experiencing food purchasing difficulties (aOR: 2.53, 95% CI: 1.87–3.42). Households in debt and those with children and lactating women also faced higher food insecurity risks. Similarly, displaced individuals in collective centers had 1.94 times the odds of reducing portion sizes (aOR: 1.94, 95% CI: 1.12–3.29). Female-headed households and households with lactating women also experienced higher rates of portion size reduction, while higher-income households were less likely to face such issues.ConclusionOur findings underscore the critical need for targeted humanitarian interventions to address food insecurity among displaced populations in conflict settings. Displaced individuals, especially those in collective centers, faced higher risks of food insecurity, compounded by household vulnerabilities such as debt, children, and lactating women. Female-headed households were particularly affected, necessitating gender-sensitive humanitarian interventions.